Secure Marketing Website - Sabeb, A. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The  Internet  provides business  with  new methods of reaching  and interacting with Â·customers as  well as  improving inter  and  intra  business communication.In  this  research, a  soft.ware  marketing web  site  with  a securitytools   is  designed  and   implemented  to  protect   the  customer  pers.onal information  and   payment   information  when  a  customer   tries  to  pay  a software package.A  new   protectior.t method   is suggested  to  protect  the  c.ustomer payment  information passing through  the  network.  This  method  is ca:Jied a covert  channel , because  it use two ports to send and receive  the paymentinformation  and  downlqads of oftware packages to the  customer  andthese ports are dynamical and changes  every time.The  modern  techniques are  used  in  building the web  site  and  its security like ASP. NET, XML with their security rules, SQL database management, JavaScript  and  Visual   Basic Script  for-  encryption  and controlling the  communication  operation,  and  Cookies   for  the  chosen ports of covert  channel.The  encryption  technique (MD5  technique) is  also   used  to  protect   the important     information   and    payment     pages    transfer    between    both directions.